Exploring the Potential of Alcohol-Fermenting Yeast Isolated from Heterotrigona itama Stingless Bees for Beverage Production - Chaijak, Pimprapa; Kongthong, Alisa; Maenpaa, Chiraprapha (Makara Journal of Science, 2024)
Mead, an ancient alcoholic beverage, relies on the indigenous microbial community in honey for alcohol fermentation. Nevertheless, data on the use of bee indigenous flora for mead production in Thailand are scarce. This investigation involved the isolation of alcohol-producing yeast strains from the Thai stingless bee species Heterotrigona itama. Subsequently, these isolated yeast strains were employed in mead fermentation with honey sourced from the same stingless bee species. Findings revealed that the yeast strain denoted as P03b, which was identified molecularly as Saccharomyces cerevisiae, exhibited the highest alcohol production of 13.53% ± 0.76%. Furthermore, the yeast strain P03b demonstrated notable stress tolerance, including resistance to elevated osmotic pressure (30% w/v glucose), extreme pH conditions (pH 2), and high ethanol content (20% w/v). In mead fermentation, the highest observed alcohol concentration reached 10.20% ± 0.26%. The resultant mead had a pH of 3.54% ± 0.04% and total reducing sugar content of 0.04 ± 0.00 mg/mL. This study provides new knowledge on using indigenous yeast in Thai stingless bee combs for alcohol beverage production.